The love that split the world - Henry, Emily (Razorbill, an imprint of Penguin Random House, 2016)
At the beginning of her last summer in Kentucky before leaving for college, Natalie is once again visited by the apparition she calls "Grandmother" and meets a new boy, Beau, who changes her life.